Duodenal duplication cyst masquerading as a pancreatic abscess in a cat. Issue 3 (26th August 2020) - Tryon, Emily; Kalamaras, Alexandra; Yang, Ching; Wavreille, Vincent; Selmic, Laura Elizabeth
Abstract : This report details a cat with a duodenal duplication cyst in the region of the right distal pancreas. The cat presented with vomiting, anorexia, pancreatitis and a palpable abdominal mass that was visible on abdominal ultrasound as a thick‐rimmed, cavitated structure with echogenic contents. As such, an initial clinical diagnosis of pancreatic abscess or cyst was suspected. After an exploratory coeliotomy to assess the lesion, a definitive diagnosis of duodenal duplication cyst was determined based on the histopathological findings of a wall with features of the intestinal tract and no communication with the intestinal lumen. The clinical signs, physical examination findings and advanced imaging characteristics of pancreatic abscess and duodenal duplication cyst are discussed in this report to aid clinicians with differentiating between these two rare lesions.